QTL analysis of early flowering of female flowers in zucchini (Cucurbita pepo L.) - Shu-ping QU; Dan YANG; Hai-yang YU; Fang-yuan CHEN; Ke-xin WANG; Wen-qi DING; Wen-long XU; Yun-li WANG (Journal of Integrative Agriculture, 2023)
Early flowering promotes early maturity, production, and the capacity to counteract biotic and abiotic stresses, making it an important agronomic trait in zucchini. The present study demonstrated that the zucchini inbred line ‘19’ consistently flowered early, taking significantly fewer days to bloom the first female flower (DFF) than the inbred line ‘113’. Genetic analysis revealed that DFF, an inheritable quantitative trait, is controlled by multiple genes. Based on the strategy of quantitative trait locus (QTL) sequencing (QTL-seq) combined with linkage analysis, three QTLs for DFF were identified on chromosomes 4, 11, and 20. This study used additional F2 populations grown under different environmental conditions for QTL mapping analysis of DFF with insertion/deletion (InDel) markers to validate these results. Using the composite interval mapping (CIM) method of R/qtl software, we only identified one major locus under all environmental conditions, located in a 117-kb candidate region on chromosome 20. Based on gene annotation, gene sequence alignment, and qRT-PCR analysis, we found that the Cp4.1LG20g08050 gene encoding a RING finger protein may be a candidate gene for the opposite regulation of early flowering in zucchini. In summary, these results lay a foundation for a better understanding of early flowering and improving early flowering-based breeding strategies in zucchini.